Comprehensive policies and programmes for livestock development in Africa: Problems, constraints and necessary future action - International Livestock Centre for Africa (International Livestock Centre for Africa, 1985)
Discusses the problems of livestock development in Africa - at producer, government and funding agency level; the basic constraints and planning approaches to livestock development; land tenure policies; livestock marketing & pricing policies; animal disease control and eradication policies; and behaviour of the producer in his environment.